Evaluating first aid knowledge among primary teachers and service evaluation in government schools, Visakhapatnam, India - Peddinti, Lakshmi Prasanna Srimathirumala; Agiwal, Varun; Rangaraju, Sai Madhuri; Chaudhari, Sirshendu (International Journal Of Community Medicine And Public Health, 2025)
Background: Ensuring school children’s safety is crucial due to their susceptibility to illnesses/injuries and limited ability self-protect. Teachers serve as vital role in the absence of immediate medical assistance, highlighting the importance of basic first-aid training and preparedness for various health emergencies to safeguard students’ well-being. Therefore, this study assessed the level of first-aid knowledge among government primary school teachers in Vishakhapatnam, India. Methods: A cross-sectional study was conducted to assess first-aid knowledge among primary teachers in government schools in urban Visakhapatnam. Cluster sampling was employed to select schools, followed by simple random sampling within each selected school to choose teachers. Quantitative phase considered a semi-structured, validated online questionnaire developed by Tech Mahindra Foundation and service evaluation involved discussion with principals. Results: Among 133 participants, 65 (48.87%) held postgraduate degrees and majority 91 (68.42%) were female. 93.23% (n=124) were familiar with first-aid procedures but only 78 (58.65%) completely unaware when to replace a first-aid kit. A higher proportion of males demonstrating good knowledge compared to females (P value = 0.031). Study suggested adding items to first-aid kits and implementing safety signage boards. Participants recommended formal first-aid training by government, NGOs, or healthcare professionals to enhance skills and knowledge. Conclusions: The study revealed high first-aid knowledge among primary teachers, but identified gaps in supply replacement and specific emergency responses. These findings are crucial for enhancing safety and improving first-aid knowledge, highlighting the importance of collaboration between teachers and parents through first aid awareness sessions to effectively respond to medical emergencies at school and home.